Video Streaming Over Publish/Subscribe - Oliveira Neto, João Martins de; Silva, Lincoln David Nery e (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Mobile technologies have created a lot of challenges for distributed systems over the last decade. Intermitent connections and weak network signals can induce unnexpected behaviour in some applications. One kind of application that suffer from these difficulties is video streaming. This paper investigates the use of SDDL, a publish/subscribe middleware based on DDS, for live video streaming. Since SDDL is designed for scalable communications in a dynamic environment, we believe the proposed solution is fit for use in mobile networks.